2018
DOI: 10.1038/aps.2018.22
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of human amniotic epithelial cells in a serum-free system and their safety evaluation

Abstract: Human amniotic epithelial cells (hAECs), derived from the innermost layer of the term placenta closest to the fetus, have been shown to be potential seed cells for allogeneic cell therapy. Previous studies have shown a certain therapeutic effect of hAECs. However, no appropriate isolation and culture system for hAECs has been developed for clinical applications. In the present study, we established a serum-free protocol for hAEC isolation and cultivation, in which better cell growth was observed compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 39 publications
3
67
0
Order By: Relevance
“…Besides the consideration of animal serum-derived contamination, our previous work also confirmed that neither acute nor long-term toxicity response is triggered by hAESC injection in xenogeneic transplantation [ 29 ]. Specifically, little change in T cell population and corelated cytokines is observed after high-dose (10 8 cells/kg) hAESC injection into mice, indicating that hAESCs do not disturb the immune system.…”
Section: The Safety Evaluation Of Human Amniotic Epithelial Stem Cmentioning
confidence: 60%
See 1 more Smart Citation
“…Besides the consideration of animal serum-derived contamination, our previous work also confirmed that neither acute nor long-term toxicity response is triggered by hAESC injection in xenogeneic transplantation [ 29 ]. Specifically, little change in T cell population and corelated cytokines is observed after high-dose (10 8 cells/kg) hAESC injection into mice, indicating that hAESCs do not disturb the immune system.…”
Section: The Safety Evaluation Of Human Amniotic Epithelial Stem Cmentioning
confidence: 60%
“…However, serious concern has been raised about the utilization of animal serum in clinical applications. To establish a more effective protocol for hAESC culture in accordance with current guidelines for clinical use, our lab developed a serum-free system for hAESC isolation and culture [ 29 ]. In brief, hAESCs are cultured with complete culture medium containing F12/DMEM, 10% KSR (KnockOut Serum Replacement), 2 mmol/L L-glutamine, 1% nonessential amino acids, 55 ÎŒmol/L 2-mer-captoethanol, 1 mmol/L sodium pyruvate, 1% antibiotic–antimycotic, and 10 ng/mL EGF.…”
Section: The Establishment Of Serum-free Culture System For Human mentioning
confidence: 99%
“…Instead, serum-free culture systems were recently reported to stabilize the quality and the purity of the cell population. 17 As an outcome, these features can improve reliability, reproducibility, and robustness of the manufacturing process and be more predictive of the in vivo outcome.…”
Section: Significance Statementmentioning
confidence: 99%
“…Indeed, the use of platelet lysate or serum may have a proliferative effect, but involves an uncontrolled cocktail of factors introducing issues with repeatability, potency, and control of the process. Instead, serum‐free culture systems were recently reported to stabilize the quality and the purity of the cell population . As an outcome, these features can improve reliability, reproducibility, and robustness of the manufacturing process and be more predictive of the in vivo outcome.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hAECs are capable of differentiation into osteoblasts [4], insulin-producing 3D spheroids [5], granulosa cells [6], corneal epithelial cells [7], hepatic cells [8], progenitor of cortical neurons [9], and pancreatic lineage [10]. hAECs have a characteristic of immune privilege due to a low expression of surface marker major histocompatibility complex, class II, DR (HLA-DR) [11]. Many studies have showed that hAECs have therapeutic potential on multiple sclerosis, immunomodulation, inflammation suppression, angiogenesis promotion, oxidative stress inhibition, neurogenesis induction, matrix metalloproteinases regulation, and remyelination stimulation [12-14].…”
Section: Introductionmentioning
confidence: 99%